Treasure Island - Stevenson, Robert Louis; Parreño, Fran (Usborne London, 2014)
When Jim Hawkins sets sail searching for buried treasure and adventure, he finds himself caught up in a deadly mutiny where he must outwit the cunning pirate Long John Silver in order to stay alive